The Effect Of Cash Turnover, Number Of Customers, Leverage And Receivable Turnover On Profitability - Ni Nengah Seri EKAYANI; I Gede Ary PUTRAWAN; AA Ayu Erna TRISNADEWI (Indonesia Strategic Sustainability, 2022)
The purpose of this study is to empirically examine the effect of cash turnover , number of customers, leverage and receivables turnover on profitability at LPD Seririt District. The location of this research is the Village Credit Institution (LPD) in Seririt District. The object of the research is cash turnover , number of customers, leverage and receivables turnover on profitability at LPD Seririt District. The population in this study is the LPD of Buleleng Regency, totaling 169 LPD. From a population of 169 LPDs in Buleleng Regency, because the object in this study uses Seririt sub-district, the sample is in study this is whole LPD which there is in Subdistrict seririt, So the sample in this study took 25 samples of LPDs in Seririt District, which met the following sample criteria for all LPDs in Seririt District registered in the LPLPD of Buleleng Regency. The analysis technique used is multiple regression analysis. The results showed that Cash Turnover , Number of Customers, Leverage and Accounts Receivable Turnover had a positive effect on profitability at the Village Credit Institution (LPD) in Seririt District in 2018-2021.